Periodontal complications of hyperglycemia/diabetes mellitus: Epidemiologic complexity and clinical challenge. Issue 1 (9th September 2018) - Kocher, Thomas; König, Jörgen; Borgnakke, Wenche Sylling; Pink, Christiane; Meisel, Peter
Abstract: This report provides a comprehensive overview of the adverse effects of hyperglycemia on the periodontium. It combines data from literature reviews of original data from two large, population‐based epidemiologic studies with comprehensive periodontal health assessment. Emphasis is placed on the exploration of hitherto sparsely reported effects of prediabetes and poorly controlled (uncontrolled) diabetes, in contrast to the umbrella term "diabetes." This stems from the realization that it is not simply having a diagnosis of diabetes that may adversely affect periodontal health. Rather, it is the level (severity) of hyperglycemia that is the determining factor, not the case definition of the diagnosis of diabetes or the type of diabetes in question. Importantly, based on existing evidence this paper also attempts to estimate the improvements in periodontal probing depth and clinical attachment level that can be expected upon successful nonsurgical periodontal treatment in people with chronic periodontitis, with and without diabetes, respectively. This exploration includes the implentation of new systematic reviews and meta‐analyses that allow comparison of such intervention outcomes between hyperglycemic and normoglycemic subjects. Based on both existing literature and original analyses of population‐based studies, we try to answer questions such as: Is there a glycated hemoglobin concentration threshold for periodontitis risk? Does short‐term periodontal probing depth reduction and clinical attachment level gain after scaling and root planing depend on glycemic control in type 2 diabetes? Are short‐term scaling and root planing outcomes in people with hyperglycemia/diabetes inferior to those in people without diabetes? Do periodontitis patients with diabetes benefit more from the use of adjuvant antibiotics with nonsurgical periodontal treatment than people without diabetes? Does hyperglycemia lead to greater tooth loss in patients in long‐term post‐periodontal treatment maintenance programs? Throughout this review, we compare our new findings with previous data and report whether the results of these new analyses corroborate, or are in discord with, similar scientific reports in the literature. We also explore the potential role of dental health‐care professionals in helping patients control the risk factors that are identical for periodontitis and diabetes. Finally, we suggest various topics that still need exploration in future research.